1999
DOI: 10.1177/003693309904400307
|View full text |Cite
|
Sign up to set email alerts
|

Polaroid Photographic Referral for Skin Cancer — A Potentially Useful Method of Reducing Time to Surgery

Abstract: A prospective trial was conducted on twenty-five patients referred by dermatologists during 1998 using a referral letter and an accompanying polaroid photograph for prospective plastic surgical management of skin cancers. Using the description and the photograph, suitable patients were given dates for operation without requiring a plastic surgery out-patient clinic appointment. This enabled, not only a saving in the cost of an out-patient appointment, but a significant reduction in waiting time to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Clinical photography has been shown to be useful in triaging and monitoring suspected skin cancers 6–9 . We have shown that digital photography is useful in downgrading otherwise urgent referrals, thus potentially improving waiting times for treatment of genuine skin cancers.…”
Section: Diagnoses Made After Photographic Evaluation and At Clinic Vmentioning
confidence: 94%
“…Clinical photography has been shown to be useful in triaging and monitoring suspected skin cancers 6–9 . We have shown that digital photography is useful in downgrading otherwise urgent referrals, thus potentially improving waiting times for treatment of genuine skin cancers.…”
Section: Diagnoses Made After Photographic Evaluation and At Clinic Vmentioning
confidence: 94%